_zgj

80 Reputation

5 Badges

9 years, 312 days

MaplePrimes Activity


These are questions asked by _zgj

T := Typesetting[delayDotProduct](sqrt(2/3), Matrix(3, 3, {(1, 1) = cos(omega*t), (1, 2) = cos(omega*t-(2/3)*Pi), (1, 3) = cos(omega*t+(2/3)*Pi), (2, 1) = -sin(omega*t), (2, 2) = -sin(omega*t-(2/3)*Pi), (2, 3) = -sin(omega*t+(2/3)*Pi), (3, 1) = 1/sqrt(2), (3, 2...

How can I simplify the following expression

sin(x+pi/4)+cos(x+pi/3)

to the following form

A*sin(x+B) or A*cos(x+B)

where A and B are calculated constant

 

How do I convert the following trigonometric expression?

sin(A)+sin(B)->2sin(A+B)/2*cos(A-B)/2

I want to simplify the following trigonometric expression

sin(x)*1/2+cos(x)*sqrt(3)/2

to

sin(x+pi/3)

how can I complete this procedure?

1 2 3 Page 3 of 3